Defanging the Nanny State - Christopher Snowdon (Institute of Economic Affairs (IEA), 2024)
What would government regulation of food, alcohol, vaping, tobacco and soft drinks look like in a more liberal Britain? There would be a lot less of it, naturally, but there would not be none. An ultra-libertarian approach would be to remove all sin taxes, abolish all health warnings, legalise all drugs, abolish age limits and sack every public health worker. But let us be realistic. Britain has been awash with nanny state policies for the last twenty years. Some of them are popular, and several of them can be justified on economic grounds. Rather than endorse a free-for-all, this paper sets itself the more modest task of making the UK the freest place in Europe for people who want to eat, drink, smoke and vape without being punished by the state. Every two years I edit the Nanny State Index, a league table of 30 European countries showing how they compare with regard to the over-regulation of food, soft drinks, alcohol and nicotine products. None of these countries is a libertarian utopia by any stretch of the imagination. Public health paternalism exists in them all, not least because of EU regulation. But there is a wide variation between the freest and most paternalistic nations. Germany and the Czech Republic have been the best performers in recent years and sit at the bottom of the table, while the top of the table is dominated by countries in Scandinavia and Eastern Europe. The UK has always been in the top half, with high scores for everything except e-cigarette regulation. At the end of this paper, we will look at what needs to be done to get the UK to the bottom of the league table and make it the best country in Europe for lifestyle freedom, but first we need to define our terms and ask what problem we are seeking to solve.
Keywords: 330